Enhancing Police Performance through Emotional Intelligence and Engagement: Learning Capacity as a Mediator - Manalu, Rejoice Benedicto; Basir, B; Setyabudi, Chairul Muriman (Journal of Economics and Management Scienties, 2025)
This study aims to determine the mediating effect of learning capacity on emotional intelligence and engagement to improve the performance of Riau Regional Police members. This study used survey and questionnaire techniques to collect respondents' answers. A total of 157 respondents' answers were collected. Data analysis was performed using SEM-PLS 4.0 software to test validity and reliability. The Upsilon V test was used to examine the effect of learning capacity as a mediating variable. The results of the study indicate that there is a significant influence of emotional intelligence on performance and engagement on performance. Furthermore, emotional intelligence has a significant influence on learning capacity, engagement has a significant influence on learning capacity, and there is a significant influence of learning capacity on performance. Additionally, learning capacity is able to mediate the relationship between engagement and performance. However, learning capacity is not yet able to mediate the relationship between emotional intelligence and performance.